NON STRIPPING INDUCED BREEDING OF CHINESE GRASS CARP CTENOPHARYNGODON IDELLA (VALENCIENNES) IN CIRCULAR CHINESE HATCHERY USING OVATIDE - GUPTA, KADAMBARI; SHARMA, ARTI; BHUSHAN, BHARAT (Journal of the Inland Fisheries Society of India, 2022)
History of pond fish culture reveals that traditional fish seed collection from riverine resources has been replaced since the advent of induced breeding techniques through the use of hormones. Also the common practice of usage of fish pituitary extract for the induction of breeding too has emerged as a lesser alternative following the availability of synthetic hormone analogues(Gn-RH) viz., sumaach, ovaprim and the latest candidate in this respect is ovatide.These have been used with success both for Indian as well as exotic Chinese carp. Among Chinese carps, grassÂ carpÂ Ctenopharyngodon idella was introduced globally from erstwhile USSR and China (Shireman and Smith, 1983) with the main objective to check unlimited growth of weeds in the aquatic ecosystems.